Table grape ‘BRS Vitória’ yield performance, vigor, and quality as influenced by rootstocks in a subtropical region - Callili, Daniel; Tecchio, Marco Antonio; Sánchez, Camilo André Pereira Contreras; Neto, Francisco José Domingues; Bonfim, Filipe Pereira Giardini; Silva, Marcelo de Souza; Leonel, Sarita; Lima, Giuseppina Pace Pereira; Campos, Olivia Pak (Australian journal of crop science, 2025)
Given the growth of vine orchards to new areas and the need for diversification of scion and rootstock combinations in subtropical sites, selecting the right rootstock can bring significant benefits to the scions. Thus, the current study sought to determine the impact of rootstocks 'IAC 572' Jales, 'IAC 766 Campinas' and '1103 Paulsen' on the productive performance, vigor, and quality of 'BRS Vitória' grapevines grown under subtropical circumstances. The experimental design was a randomized block design, with three treatments (rootstocks), seven blocks, and three plants per plot, for a total of 63 grapevines. Over three summer seasons (2020, 2021, and 2022), production and vigor components (number of clusters per vine, production per vine, productivity, and pruning mass), physical-chemical properties of clusters and berries (number of berries, fresh mass, length, and width of clusters and berries, soluble solids, pH, titratable acidity, and maturity index, as well as the quantities of bioactive chemicals in the berries (phenols, flavonoids, and anthocyanins), were all assessed. The rootstocks had a significant influence on the majority of the factors studied. The results showed that increasing vigor of rootstock increased vine yield while decreasing the quantity of soluble solids and bioactive chemicals in grapes. The 'IAC 572' rootstock increased vigor and productivity, whereas grapes from plants grafted onto '1103P' exhibited higher amounts of soluble solids, phenols, flavonoids, and anthocyanins. Overall, the 'BRS Vitória' cultivar demonstrated high yield and quality. As a result, extending cultivation in subtropical locations emerges as an effective solution to meet the growing demand for seedless grapes.